Women's education in The Perspective of Islamic Philosophy of Education: A Theoretical Analysis of the Essence and Challenges of Emancipation in the Age of Disruption - Rabiatul Adawiyah; Salminawati Salminawati; Usiono Usiono (STAI Serdang Lubuk Pakam, 2023)
This research aims to analyze women's education in the perspective of Islamic education philosophy with two focuses of study, namely the essence and challenges of emancipation in the era of disruption. This research uses a qualitative method based on library research. The data analysis used is content analysis. The results revealed that by nature women have a position as a housewife, as a wife, both of which make her a good teacher for herself and her children, and an educator partner for her husband. At the age of children, women's education is oriented towards their growth and development for their basic potential. At the age of adolescence leads to the formation of personality, and at adulthood leads to education for her duties as a mother and shaper of generations. The emancipation of women in the era of disruption in the context of Islamic education philosophy reflects the transformation of the role and rights of women in a changing society. In the framework of Islamic thought, education is the main key to understanding the values of gender equality as contained in Islamic teachings. The process of women's emancipation illustrates the effort to free women from limitations and inequality, with Islamic education as a means to empower them intellectually and spiritually.